Turmeric - maize and onion intercropping systems. IV. PAR interception - PALANIAPPAN, K SIVARAMAN, S P (Journal of Spices and Aromatic Crops, 1996)
Experiments conduded at Coimbatore (Tamil Nadu, India) to study the pattern of interception of photosynthetically active radiation in intercropping systems with turmeric (Curcuma longa) - maize (Zea mays) and onion (Allium cepa) indicated that with a high maize population, the mixed canopy could effectively intercept more of available photosynthetically active radiation throughout the growing season, than the sale crop of turmeric, maize or onion.